2004
DOI: 10.1111/j.1365-2842.2004.01377.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an interocclusal appliance on bite force and masseter electromyography in asymptomatic subjects and patients with temporomandibular pain and dysfunction

Abstract: The aims of this study were to assess the effect of clenching with or without the presence of an interocclusal appliance (IOA) on bite force (BF) and masseter electromyography (EMG) in patients with temporomandibular pain dysfunction disorders (TMPD) and to compare these results with an asymptomatic age- and gender-matched control group. Ten patients with TMPD (mean age 26.9 years) were compared with eight healthy controls (mean age 25.3 years). Bilateral masseter EMG activity was recorded at rest, while clenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
13

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 38 publications
(60 reference statements)
2
28
1
13
Order By: Relevance
“…The association between the presence of TMD and reduced MBF is contradictory in the literature and may be dependent on the severity of the TMD in the given sample (14)(15)(16)(17). Our results agree with those of previous studies (2,18,19), where no association between TMD and bite force was observed, and neither subjective symptoms nor clinical signs of TMD correlated significantly with MBF values (14).…”
Section: Resultssupporting
confidence: 81%
“…The association between the presence of TMD and reduced MBF is contradictory in the literature and may be dependent on the severity of the TMD in the given sample (14)(15)(16)(17). Our results agree with those of previous studies (2,18,19), where no association between TMD and bite force was observed, and neither subjective symptoms nor clinical signs of TMD correlated significantly with MBF values (14).…”
Section: Resultssupporting
confidence: 81%
“…18 It was stated that the effectiveness of splints is achieved by redistributing the oral forces 19 or reducing the hyperactivity of the muscles. 13,20,21 Many studies evaluated the efficiency of occlusal splints 11,13,14,19,20 ; however, an optimal occlusal splint thickness was not defined in any of them. The occlusal splint thickness is an important consideration when treating patients and may directly influence the clinical effects.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,8,9 Decreased EMG activity of the jaw muscles with an increased jaw opening is one of the hypotheses that explains the clinical efficiency of occlusal splints for treating masticatory muscle hyperactivity generally seen in patients with temporomandibular (TMD) disorders and bruxism. 1,10,11 It was suggested that adjusting the thickness of splints to or near the vertical dimension that produced the least EMG activity may be effective in reducing masseteric muscle hyperactivity and related symptoms. 1 It is assumed that insertion of an occlusal splint increases the jaw opening, helps relax muscles, 12,13 and redistributes intraoral forces more evenly throughout the masticatory system.…”
Section: Introductionmentioning
confidence: 99%
“…Jest on zaopatrzony w wał nagryzowy, który kontaktuje w jednym miejscu z przyśrodkowym zębem siecznym dolnym, prostopadle do długiej osi zęba. [17][18][19][20] Wskaźnik ten, jak i jego modyfikacje, działają na zasadzie obronnego odruchu nocyceptywnego z receptorów czuciowych nerwu trójdzielnego znajdują-cych się w obrębie dolnych zębów przednich. 6 Nagryzanie na twardy wskaźnik hamuje aktywność mięśni przywodzących żuchwę i aktywuje mięśnie odwodzące, na skutek czego powstaje ochronna równowaga mięśniowa.…”
Section: Deprogramacja Mięśniunclassified